The case for a multilateral or plurilateral framework on investment - Wenhua Shan (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
With converging investment agreement practice and increased participation of developing countries in the investment regime, the time is right to reconsider a multilateral or plurilateral framework on investment. This Perspective discusses how existing institutions could contribute to its focus, establishment, and governance.
Keywords: 330